Pertanggungjawaban Pidana Bagi Pelaku Pelanggaran Hak Ekonomi Pencipta (Studi Kasus Putusan Nomor 2504/Pid.Sus-2022/Pn.Mdn) - khadapi, rio; Maswandi, Maswandi; Sitorus, Nanang Tomi (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This article or paper aims to analyze the Legal Arrangements for the Violation of the Creator's Economic Rights Problems and Legal Consequences for the Violation of the Creator's Economic Rights, as well as analyze the Criminal Liability for Perpetrators of Violations of the Creator's Economic Rights. This research uses normative juridical research methods, data collection techniques, namely literature research, field research (PN Medan). The results of the study show that Law Number 28 of 2014 concerning Copyright (UUHC) provides strong protection for the economic rights of creators through civil and criminal law mechanisms. However, violations such as piracy remain a challenge that requires more effective law enforcement. The case of Decision Number 2504/Pid.Sus/2022/PN.Mdn shows the importance of strict punishment to provide a deterrent effect and increase awareness of copyright protection. Criminal liability for perpetrators of infringement is the key to protecting copyright, but its success depends on public awareness, effective supervision, and consistency of law enforcement. Cross-sector collaboration and the use of technology are needed to support copyright respect and the sustainable growth of the creative industry.